Nitrogen-use efficiency: trade-offs between N productivity and mean residence time at organ, plant and population levels (Functional Ecology, 2004)
* 1Nitrogen-use efficiency (NUEN) is often decomposed into the product of N productivity (AN) and the mean residence time of N (MRTN). Theory suggests a trade-off between both components, but direct experimental evidence is still scarce. A field study with young trees of the evergreen Quercus ilex and the marcescent-evergreen Quercus faginea was carried out to test this trade-off through analysis of plant traits at organ, whole-plant and population levels. * 2Specific leaf area (SLA) was the main trait positively related to AN in Q. faginea. By contrast, greater litter production and consumption by caterpillars resulted in larger N losses and shorter MRTN in Q. faginea. Early leaf senescence in Q. faginea produced leaf litter with high N concentration that contributed significantly to N loss. Moreover, Q. ilex had higher plant survivorship. The inverse relationship between leaf longevity and SLA is probably a key component of the trade-off between N losses and plant N productivity. * 3Quercus faginea had greater N uptake from soil, linked to its longer specific root length of fine roots and greater biomass allocation to underground tissues. Smaller N losses in Q. ilex compensated for its smaller N uptake and allowed a similar N balance at whole-plant level. * 4Our results support the hypothesis of a trade-off between AN and MRTN. Quercus ilex had a long MRTN, while Q. faginea has a high AN, and vice versa. The long MRTN in Q. ilex involves not only reduced N loss through long intrinsic leaf life span, but also resistance to harsh environmental factors and defence against herbivores. This suggests that a long MRTN is a potentially successful strategy in nutrient-poor environments.

Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.

Leaf life span differs from retention time of biomass and nutrients in the crowns of evergreen species (Functional Ecology, 2003)
* 1A long leaf life span has been interpreted as an adaptation to low nutrient availability. It is commonly assumed that a long leaf life span permits a longer utilization of nutrients in the leaf biomass and that this contributes to improving nutrient use efficiency. However, a long leaf life span is also associated with other leaf traits that reduce instantaneous productivity, which might reduce the growth rate of the leaf biomass and shorten the functional life of the leaf. * 2We studied the relationships between leaf life span and the retention time of biomass and nutrient pools in several woody species with different leaf life spans. We measured the monthly variations in the total number of leaves per annual shoot, mass per leaf, and N and P contents per leaf. With these data, the leaf life span and the mean residence time (MRT) of leaf biomass and nutrient pools were estimated. * 3The increase in the total number of leaves was fast in all species studied at the start of the growth season. In contrast, in evergreen species mass per leaf and total N and P contents per leaf increased gradually after the first year of life of the leaves, and the maximum mass and nutrient contents per leaf were attained only towards the end of the lifetime of the leaves. * 4Owing to the delay in the development of mass and nutrient pools with respect to leaf number dynamics, in evergreen species leaf life span was longer than the MRT of leaf biomass and nutrient pools because part of the leaf biomass and nutrient pool remained in the crown for a shorter time than the mean duration of the individual leaves. * 5The differences between leaf life span and the MRT of the biomass and nutrients increased with leaf life span. The slow growth of evergreen leaves therefore contributes to reduce the adaptive value of a long leaf life span as a mechanism to increase the duration of the photosynthetic machinery.

Pre-climax epiphyte communities of bryophytes and lichens in Mediterranean forests from the Central Plateau (Spain) (Plant Ecology, 1996)
The pre-climax epiphytic communities of forests from the Spanish Mediterranean region (Central Plateau) were studied by numerical and traditional floristic methods. One hundred phytosociological relev6s were analyzed through a classical numerical approach based on hard partitions improved by PCoA - Principal Coordinates Analysis - ordinations. Two groups easily related to two different suballiances included in Frullanion dilatatae Lecointe 1975, Ulotenion crispae (Barkman 1958)Lecointe 1975 and Fabronienionpusillae Barkman 1958 were detected. Two new syntaxa within the ass. Ortotrichetum lyeUii (Allorge 1922) Lecointe 1975 are proposed. Phytogeography, syntaxonomy and ecology of these communities are discussed.

Effects of leaf longevity and retranslocation efficiency on the retention time of nutrients in the leaf biomass of different woody species - Escudero, a; Arco, J. M.; Sanz, I. C.; Ayala, J. (Oecologia, 1992)
A study was made of the retention times of N and P in the leaf biomass and their relationship with the retranslocation percentages and the leaf longevities in some woody species in Central Spain. The retention times of both nutrients were strongly related to the nu- trient status of each species. These results suggest that a prolonged retention time is a way of increasing nutrient use efficiency in conditions of low nutrient availability. Plants can increase the retention time of nutrients in their leaf biomass by means of an increase in leaf longevity and/or by means of an increase in retranslocation effi- ciency. However, the effect of the retranslocation effi- ciency on retention times was almost negligible compared with the effect of leaf longevity. This suggests that an increase in leaf longevity is probably the best adaptation for increasing efficiency in the use of nutrients.
Keywords: leaf longevity; nitrogen; Nutrient use efficiency; phosphorus; retranslocation

The efficiency of nitrogen retranslocation from leaf biomass in Quercus ilex ecosystems (Plant Ecology, 1992)
Nitrogen retranslocation from senescing leaves represents a crucial adaptation by tree species towards a more efficient use of this nutrient. As a result, this part of the nitrogen cycle has received increasing attention in recent years. However, there remain strong discrepancies with respect to the factors re- sponsible for interspecific differences in the efficiency of this process. In the present work the seasonal pattern of leaf growth and the movement of nitrogen in leaves have been studied in a series of Quercus ilex plots with different levels of rainfall and soil quality in central- western Spain, as well as in 20 other woody species typical of this area. The percentage of nitrogen retranslocated was estimated from the difference between the maximum mass of nitrogen stored in the leaf biomass and the amount of this nutrient returned annually to the soil through leaf fall. Q. ilex appears as one of the least efficient species in the Mediterranean region in the recovery of nitrogen from senescing leaves (29.7°0 of the maximum pool). Furthermore, the older leaves of Q. ilex do not s h o w the cycles of nitrogen withdrawal during new flushes of shoot growth, such as occurs in Pinus spp. This suggests that older leaves in Q. ilex do not play an important role as nitrogen storage organs.